2022
DOI: 10.1039/d2sc01160c
|View full text |Cite
|
Sign up to set email alerts
|

Polyoxometalate steric hindrance driven chirality-selective separation of subnanometer carbon nanotubes

Abstract: Subnanometer single-chirality single-walled carbon nanotubes (SWCNTs) are of particular interest in multiple applications. Inspired by the interdisciplinary joint of redox active polyoxometalates and SWCNTs, here we report a cluster steric...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 79 publications
0
9
0
Order By: Relevance
“…Single-walled carbon nanotubes (SWCNTs), whose structure is indexed by two integers ( n , m ) (the so-called “chiral index”), could be a typical example of this aspect. To fully utilize the chirality-dependent outstanding performance of SWCNTs, the synthesis of nanotubes with identical ( n , m ) has been considered as an ultimate goal, which is, however, a considerable challenge. …”
Section: Introductionmentioning
confidence: 99%
“…Single-walled carbon nanotubes (SWCNTs), whose structure is indexed by two integers ( n , m ) (the so-called “chiral index”), could be a typical example of this aspect. To fully utilize the chirality-dependent outstanding performance of SWCNTs, the synthesis of nanotubes with identical ( n , m ) has been considered as an ultimate goal, which is, however, a considerable challenge. …”
Section: Introductionmentioning
confidence: 99%
“…One-dimensional heterostructures coupled with SWCNTs have attracted tremendous attention recently. The use of CNTs as hosts has been widely demonstrated to encapsulate various guests in the cavity, such as molecules, clusters, picoperovskites, , and unusual atomic chains/crystals. , These fascinating findings have elaborately clarified the templating and shielding effects, allowing access to the unseen crystal structures ,, and dynamic events, ,,, and improving electrical performance. Moreover, the monolayer of graphite carbon of SWCNTs has also been proved to be transparent to the inner guests, which enables the guests to modulate the electronic surface structure of SWCNTs through host–guest charge communication. ,, However, the highly carbophilic metals such as W and Mo which tend to exhibit strong metal–carbon interactions , were rarely studied previously. The strong carbide-formatting elements (W, Mo) could exhibit strong interactions with carbon and result in a considerable charge communication with the host SWCNTs, providing a nondestructive way to homogeneously modify the electronic surface of SWCNTs.…”
Section: Introductionmentioning
confidence: 99%
“…47−50 Moreover, the monolayer of graphite carbon of SWCNTs has also been proved to be transparent to the inner guests, which enables the guests to modulate the electronic surface structure of SWCNTs through host−guest charge communication. 28,51,52 However, the highly carbophilic metals such as W and Mo which tend to exhibit strong metal−carbon interactions 53,54 were rarely studied previously. The strong carbide-formatting elements (W, Mo) could exhibit strong interactions with carbon and result in a considerable charge communication with the host SWCNTs, providing a nondestructive way to homogeneously modify the electronic surface of SWCNTs.…”
Section: ■ Introductionmentioning
confidence: 99%
“…[13] Yang and Li et al recently reported a cluster steric hindrance strategy by assembling POMs on the exterior of subnanometer SWNTs, and achieved the separation of chirality specific SWNTs. [15] To date, most studies focused on the assembly of POMs on the outer walls of CNTs. However, due to the inhomogeneous electron distribution inside and outside the CNTs wall, a comprehensive understanding of the assembly behavior of POMs within CNTs is of great significance.…”
Section: Introductionmentioning
confidence: 99%
“…Yang and Li et al. recently reported a cluster steric hindrance strategy by assembling POMs on the exterior of subnanometer SWNTs, and achieved the separation of chirality specific SWNTs [15] . To date, most studies focused on the assembly of POMs on the outer walls of CNTs.…”
Section: Introductionmentioning
confidence: 99%